Dinosaur natural track casts from the Lower Cretaceous Hekou Group in the Lanzhou-Minhe Basin, Gansu, Northwest China: Ichnology, track formation, and distribution. (January 2015) - Xing, Lida; Li, Daqing; Lockley, Martin G.; Marty, Daniel; Zhang, Jianping; Scott Persons, W.; You, Hailu; Peng, Cuo; Kümmell, Susanna B.
Abstract: Multiple dinosaur tracksites are known from the red beds (sandstones and siltstones) of the Hekou Group in the Lanzhou-Minhe Basin in Gansu Province, China. Among these, the most famous is the Yanguoxia No. 1 & 2 tracksite, which has an abundance of tracks from a diverse ichnofauna. Here, we describe natural casts from six new tracksites including three located near the Yanguoxia No. 1 & 2 tracksites and three from more distant tracksites (located up to 40 km from Yanguoxia). The new tracksites have all yielded isolated, large dinosaur track casts, two of which are tridactyl tracks of ornithopod and/or theropod affinity, while another eight casts are pes and manus tracks of medium-to large-sized sauropods. The predominance of sauropod track casts may reflect the fact that, by simple virtue of their large size, sauropods tracks resist weathering and are easy to find. Notably, the sauropod track casts are deep natural tracks left in soft and moist substrates with a relatively high cohesiveness. They offer a glimpse into the three-dimensional foot morphology of the sauropod trackmakers and their foot movement (locomotion), and thus are an important complement to the tracks preserved as (shallow) impressions and the trackways of the Yanguoxia No. 1 & 2 tracksite. The new tracksites suggest a lower ecological diversity than would be inferred from the Yanguoxia No. 1 & 2 tracksite. However, it is assumed that this apparent low diversity is an artifact resulting from the small sample area and the fact that all the outcrops are cross-sections where bedding planes – that could reveal small tracks and more abundant tracks and trackways – are scarce and limited to small surfaces. These new sites suggest that the distribution and frequency of dinosaur tracks within the Lanzhou-Minhe Basin is much wider than previously assumed and that many more dinosaur tracksites are likely to be discovered within the basin in the future.